PENGARUH MOTIVASI, KEPEMIMPINAN DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA PERUSAHAAN JASA PENGIRIMAN BARANG CV. MACIKA EXPRESS SEMARANG - Setyo Adhy Omara, 13.05.51.0029 (Students Journal of Economic and Management, 2017)
The study examines and examines the effect of motivation, leadership and compensation on employee performance. This research was conducted on freight forwarding company CV.Macika Express Semarang. The object of research in writing this thesis is employees CV.Macika Express Semarang. The sampling technique in this study purposive sampling amounted to 45 respondents as a sample with data collection methods using questionnaire (questionnaire) by spreading questionnaires question to respondents to obtain information. The results of this study showed that motivation has a positive and significant effect on employee performance, leadership has positive and significant effect on employee performance, compensation has positive and significant effect on employee performance. Keywords: Motivation, Leadership, Compensation and Employee Performance